NAVIGATING DISRUPTION: THE ROLE OF BUSINESS STRATEGY IN ADAPTING TO TECHNOLOGICAL INNOVATIONS AND MARKET SHIFTS - Rajab Al-Mansouri (Modern American Journals, 2025)
In the current business environment, technological innovations and market shifts are occurring at an unprecedented pace. Companies are facing constant pressure to adapt to new technologies, shifting consumer behaviors, and evolving competitive landscapes. This paper explores the critical role that business strategy plays in helping organizations navigate these disruptions. By analyzing real-world examples of companies that have successfully adapted to digital transformation, artificial intelligence, and the shifting dynamics of global markets, the paper identifies key strategic frameworks and approaches that businesses can adopt to maintain a competitive edge. It also examines the challenges associated with these disruptions and presents strategies for businesses to innovate while staying agile in a rapidly changing environment.
Keywords: Business Strategy, Technological Innovation, Market Disruption, Digital Transformation, Artificial Intelligence, Competitive Advantage, Organizational Agility, Strategic Management, Business Innovation, Global Business